A theory of entrepreneurial opportunity identification and development - Ardichvili, Alexander; Cardozo, Richard; Ray, Sourav (Journal of Business Venturing, 2003)
This paper builds on existing theoretical and empirical studies in the area of entrepreneurial opportunity identification and development. It utilizes Dubin's [Theory Building, (second ed.). Free Press, New York, 1978.] theory building framework to propose a theory of the opportunity identification process. It identifies entrepreneur's personality traits, social networks, and prior knowledge as antecedents of entrepreneurial alertness to business opportunities. Entrepreneurial alertness, in its turn, is a necessary condition for the success of the opportunity identification triad: recognition, development, and evaluation. A theoretical model, laws of interaction, a set of propositions, and suggestions for further research are provided.